Investigation of the Influence of Hexabenzocoronene in Polyacrylonitrile-Based Precursors for Carbon Fibers - Romy Peters; Dawon Jang; Daniel Sebastian Jens Wolz; Sungho Lee; Hubert Jäger; Mirko Richter; Chokri Cherif; Kiryl Vasiutovich; Marcus Richter; Xinliang Feng; Thomas Behnisch; Maik Gude (Fibers, 2023)
For several decades, carbon fibers have been used for lightweight engineering in aircraft automotive and sports industries, mostly based on high-quality polyacrylonitrile (PAN). We investigated a novel PAN-based precursor fiber (PF) modified with a polycyclic aromatic hydrocarbon, namely hexabenzocoronene (HBC), which is expected to improve the thermal conversion process and to create a carbon fiber (CF) with enhanced mechanical properties. For this purpose, the novel PF and a spun-like homopolymeric PAN-based PF were thermally stabilized and carbonized in continuous lab-scale plants. The effect of the additive HBC on the conversion processes, fiber diameter and shape, density, and mechanical properties were investigated. The results showed that HBC seems to support stabilization reactions, and HBC/PAN-based PF show potentially higher stretchability of PF and stabilized fiber. The modified CF showed an improvement in Young’s modulus of about 25% at the same tensile strength compared to the unmodified PAN-based CF, resulting from enhanced crystalline orientation. The results showed a high potential of the HBC/PAN for energy-efficient production. In particular, the influence on tensile strength and modulus under optimized process conditions, as well as the possibility to use low quality PAN, need to be further investigated.